Kombinasi Penerapan Metode WASPAS dan Rank Order Centroid (ROC) dalam Keputusan Pemilihan Teknologi Kamera Ponsel Terbaik - Anwar, Badrul; Simatupang, Wakhinuddin; Muskhir, Mukhlidi; Irfan, Dedy; Nasyuha, Asyahri Hadi (Forum Kerjasama Pendidikan Tinggi, 2022)
Smartphone camera technology is currently growing rapidly so that it has specifications that support it so that the results obtained are almost on par with the quality of digital cameras. Supported cellphone cameras can be used in learning photography, not necessarily with a digital camera. The increasing number of cellphone choices makes users who want to study photography confused in choosing a cellphone that has the best cellphone camera technology. So that a Decision Support System was applied in this study as a system for obtaining the best cellphone camera technology decisions. In making the right decision on selecting the best cellphone camera technology, it must meet the criteria for Number of Camera Features, Number of Main Cameras, Number of Front Cameras, Main Camera Resolution, Front camera Resolution, Optical Zoom and Quality of Video Recording. Therefore a Decision Support System is needed to solve the problem by applying the ROC (Rank Order Centroid) and WASPAS (Weighted Aggregated Sum Product Assessment) methods which can produce weight and preference values from the first ranking alternative. So that the selection of the best mobile camera technology for the best mobile camera technology can be found in table 7, namely the Samsung Galaxy S22 Ultra which is in the A5 alternative with the highest score of 3.8354 as the first rank